The microbiome analysis of ripen grape berries supports the complex etiology of sour rot - Brischetto, Chiara; Rossi, Vittorio; Fedele, Giorgia (Frontiers in Microbiology, 2024)
Sour rot (SR) is a grapevine disease complex that is not completely understood in its etiology and epidemiology. Recently, SR has received special attention due to its increasing economic importance due to crop losses and reduced wine quality. In this study, the fungal and bacterial microbiota of healthy (i.e., without rot symptoms) and rotten (i.e., exhibiting visual and olfactory SR symptoms) ripe bunches were characterized across 47 epidemics (39 vineyards in six Italian grape-growing areas) over three years. The 16S rRNA gene, ITS high-throughput amplicon sequencing, and quantitative PCR were used to assess the relative abundance and dynamic changes of microorganisms associated with SR. The estimators of genera richness of fungal communities within samples indicated a significantly different diversity between healthy and rotten bunches. For bacterial communities, the healthy and rotten bunches significantly differed in the total number of species, but not in abundance distribution across species. The bunch status (i.e., healthy and rotten) was a significant source of diversity (p < 0.01) when the community composition between samples was evaluated, indicating that microbiome composition varied between healthy and rotten bunches. In particular, healthy and rotten bunches shared 43.1 and 54.8% of fungal and bacterial genera, respectively; 31.3% (fungal) and 26.2% (bacterial) genera were associated with rotten bunches only. The yeast genera Zygosaccharomyces, Zygoascus, Saccharomycopsis, Issatchenkia, and Pichia and the bacterial genera Orbus, Gluconobacter, Komagataeibacter, Gluconacetobacter, and Wolbachia were strongly associated with bunches showing SR symptoms based on a linear discriminant analysis. These microorganisms have been associated with Drosophila insects in literature. The relationships between the microflora associated with SR-affected bunches and the roles of Drosophila in SR development need further investigation, which may open perspectives for more effective disease control.